Βιβλιοκρισία:CH. GASTGEBER - E. MITSIOU - J. PREISER-KAPELLER - V. ZERVAN (eds), The Patriarchate of Constantinople in Context and Comparison. Proceedings of the International Conference Vienna, September 12th-15th 2012. In memoriam Konstantinos Pitsakis (1944-2012) and Andreas Schminck (1947-2015), Wien 2017 - ΑGORITSAS Dimitris (Byzantina Symmeikta, 2019)
Βιβλιοκρισία:Ch. Gastgeber - E. Mitsiou - J. Preiser-Kapeller - V. Zervan (eds), The Patriarchate of Constantinople in Context and Comparison. Proceedings of the International Conference Vienna, September 12th-15th 2012. In memoriam Konstantinos Pitsakis (1944-2012) and Andreas Schminck (1947-2015), Wien 2017